The monster gang - Everett, Felicity (Usborne Pub Ltd; UK, 2007)
An original story for children who have just started reading on their own. One rainy Saturday, Ellie and her friends set up the Monster Gang. But one of the gang is hiding a big secret. Will I be found out? Part of the Usborne Reading Program developed with reading experts at the University of Roehampton.